TOTAL COMMUNICATION PHENOMENA AS A UNIVERSAL PATTERN OF THE EXISTENCE OF THE INTERNATIONAL POLITICAL WORLD - Kharchenko, Y. V. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Conceptualization of the phenomenon of interaction as a key model for the existence of an international policy of peace in the context of the doctrine of universal communication phenomena is carried out. Co-evolutionary strategy for interaction is presented as an idea of co-evolution, which provides for the harmonious condition of nature and society, for a stable development of environment, in which the person resides. While all the planes of this environment, each at its own level, are demonstrating the linkage with other planes. It is shown that universal communication is evident in the natural environment, but disunity is sometimes evident in the human social world. Co-evolutionary principle of the international community provides the opportunity for equivalent partnership and cooperation. Fragmentation is the result of purposeful destruction of the infinitely varied naturally fitted connections and relationships between people. This breaks the symmetry of the universal communication phenomena.